2022
DOI: 10.3390/pharmaceutics14061252
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9-Based Technology and Its Relevance to Gene Editing in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) and other chronic and debilitating neurodegenerative diseases (NDs) impose a substantial medical, emotional, and financial burden on individuals and society. The origin of PD is unknown due to a complex combination of hereditary and environmental risk factors. However, over the last several decades, a significant amount of available data from clinical and experimental studies has implicated neuroinflammation, oxidative stress, dysregulated protein degradation, and mitochondrial dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 324 publications
0
12
0
Order By: Relevance
“…Despite these challenges, the area of a gene cure for PD is rapidly advancing, with innovative gene editing technologies. Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 offers new opportunities for precise gene modification and targeted correction of genetic mutations associated with PD [ 46 , 47 ]. By using CRISPR-Cas9, coupled to the DNA-methyltransferase 3A catalytic domain (DNMT3A), Kantor et al [ 48 ] decreased SNCA mRNA and protein in human induced pluripotent stem cell (hiPSC)-derived DNs from a PD patient with the triplication of the SNCA locus.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these challenges, the area of a gene cure for PD is rapidly advancing, with innovative gene editing technologies. Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 offers new opportunities for precise gene modification and targeted correction of genetic mutations associated with PD [ 46 , 47 ]. By using CRISPR-Cas9, coupled to the DNA-methyltransferase 3A catalytic domain (DNMT3A), Kantor et al [ 48 ] decreased SNCA mRNA and protein in human induced pluripotent stem cell (hiPSC)-derived DNs from a PD patient with the triplication of the SNCA locus.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative gene therapies are based on the overexpression of growth and/or neuroprotective factors, such as glial cell-line derived neurotrophic factor, neurturin, artemin, persephin, vascular endothelial growth factor, or Nurr1 [ 218 , 219 , 220 , 221 ]. It has also been suggested that CRISPR/CAS9 technology could be used to correct genetic mutations associated with PD [ 222 ]. Other studied approaches were based on cellular transplantation.…”
Section: New Therapies: Modulating α-Synuclein Aggregationmentioning
confidence: 99%
“…The pathological state is determined by the onset of cellular abnormalities ensuing propagation of its remarkable hallmarks, including pathological a-syn inclusions and chronic inflammation, which progresses with age. 8,9 The pathological processes and hallmarks of PD are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%